Wax Apple (Syzygium samarangense (Blume) Merr. & L.M. Perry): A Comprehensive Review in Phytochemical and Physiological Perspectives - Arnia Sari Mukaromah (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2020)
Wax apple (Syzygium samarangense (Blume) Merr. L.M. Perry) is a tropical non-climacteric fruit and belongs to Myrtaceae. It has high diversity in cultivars, metabolite content, and its biological activities. In this comprehensive review, research findings had revealed that various metabolites found in the wax apple have biological activities. The said biological activities such as: antioxidant, immunomodulatory, antibacterial, anticancer, anti-glycation, anti-inflammation, anti-hypertriglyceridemic, anti-hyperglycemic, relaxant, and spasmolytic activities. Other potential use for the metabolites also includes the treatments for neurodegenerative abnormality, analgesic, and central nervous system (CNS) depression agent. Furthermore, wax apple physiological and phytochemical characteristics can be enhanced by girdling technique, hydrogen peroxide treatment, plant growth regulators treatment, and fruit bagging treatment. Meanwhile, postharvest technology of wax apple fruit utilizes nitric oxide treatment, oxalic acid treatment, cold treatment, and Aloe vera gel coating. Wax apple has also been evolved as an ointment, anti-acne cream, and nata de guava. However, environmental stress becomes a challenge in the wax apple plantation. Therefore, the development of molecular biology, chemistry, and postharvest technology will solve those challenges. This review concludes that wax apple (S. samarangense) is a tropical fruit that promises to support the nutritional values and human health.